2019
DOI: 10.1038/s41467-019-11476-3
|View full text |Cite
|
Sign up to set email alerts
|

Maternal control of suspensor programmed cell death via gibberellin signaling

Abstract: Plant embryos are generated and develop in a stable and well-protected microenvironment surrounded by maternal tissue, which is vital for embryogenesis. However, the signaling mechanisms responsible for maternal tissue-to-proembryo communication are not well understood. Here, we report a pathway for maternal tissue-to-proembryo communication. We identify a DELLA protein, NtCRF1 ( NtCYS regulative factor 1), which regulates suspensor programmed cell death (PCD). NtCRF1 can bind to the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…3C,S5). Conflict among siblings for maternal resources is thought to drive adaptive evolution of suspensors (Geist et al, 2019), which support the developing embryo proper and can serve as a conduit for maternally derived molecules (Nagl, 1990; Robert et al, 2018; Shi et al, 2019; Stadler et al, 2005; Yeung, 1980). Because columella initials are situated between the suspensor and embryo proper, they may help regulate communication between mothers and their offspring.…”
Section: Discussionmentioning
confidence: 99%
“…3C,S5). Conflict among siblings for maternal resources is thought to drive adaptive evolution of suspensors (Geist et al, 2019), which support the developing embryo proper and can serve as a conduit for maternally derived molecules (Nagl, 1990; Robert et al, 2018; Shi et al, 2019; Stadler et al, 2005; Yeung, 1980). Because columella initials are situated between the suspensor and embryo proper, they may help regulate communication between mothers and their offspring.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in animals it has been long recognized that maternal gene products control initial pattern formation before the transition of control from the maternal to the zygotic genome (Lee et al, 2014;Tadros and Lipshitz, 2009). By contrast, transcriptional activation of the zygotic genome soon after fertilization is necessary for zygote elongation and initial divisions in Nicotiana tabacum (tobacco) (Zhao et al, 2011) and the model flowering plant Arabidopsis thaliana (Arabidopsis) (Kao and Nodine, 2019;Zhao et al, 2019). In addition, the vast majority of genes regulating Arabidopsis embryo morphogenesis are zygotically expressed (Nodine and Bartel, 2012;Zhao et al, 2019) and required (Meinke, 2019;Muralla et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As with the silencing of mcII‐Pa , additional caspase‐like activity was silenced alongside the directly targeted NtCYS‐NtCP14 activity (Zhao et al ). In a recent article, Shi et al () found that a DELLA‐family transcription factor called Nt CRF1 bound to the NtCYS promoter. DELLA proteins are typically degraded in the presence of bioactive GAs, thus linking NtCYS‐mediated suspensor termination to the GA pathway.…”
Section: The Death Of the Suspensormentioning
confidence: 99%
“…Interestingly, the expression of pNTGA3ox::H2B‐GFP constructs was found in the seed coat and the micropylar region, and not in the proembryo or suspensor, indicating that the GAs were being supplied maternally. Therefore, maternal GAs appear to trigger the degradation of Nt CRF1, which in turn reduces NtCYS expression and increases expression of NtCP14 , finally triggering suspensor PCD (Shi et al ).…”
Section: The Death Of the Suspensormentioning
confidence: 99%